Potentiodynamic characteristics of ruthenized platinum electrodes in sulphuric acid solutions - Lezna, Reynaldo Oscar (1983)
The potentiodynamic response of ruthenized platinum electrodes in 0.5 M and 12 M H2SO4 at 25°C is investigated. The E/I profiles depend on the electrode history and involve sintering-type effects. In 12 M H2SO4 they can be analysed in more detail because the separation of the H-adatom and O-electroadsorption potential ranges is greater than in 0.5 M H2SO4. Thus, four different stages related to the oxide layer are distinguished. The interpretation of the corresponding overall processes is given in terms of the equilibrium potentials of the Ru/H2O system and the reversibility characteristics of the different stages derived from the various potential/time perturbation programs are discussed through reaction patterns previously considered for these reactions on other noble metals.